2007
DOI: 10.2527/jas.2005-708
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for reproduction and production traits of Landrace sows in Thailand1

Abstract: Data from Thai Landrace sows were used to estimate genetic parameters for reproduction and production traits in first and later parities. The reproduction traits investigated were total number of piglets born per litter (TB), number of stillborn piglets (SB), and number of piglets born alive but dead within 24 h (BAD). The reproduction data pertained to 12,603 litters born between 1993 and 2005. The production measures were ADG and backfat thickness (BF); these were recorded in 4,163 boars and 15,171 gilts. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
3
22
3
3
Order By: Relevance
“…However, contrary to these study results, the estimates found by both authors declined over the intervals. Imboonta et al (2007) have reported greater heritability estimates than in the present study, using multitrait analysis. Its values were 0.16, 0.16 and 0.18 for the first, second and third WEI, respectively.…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…However, contrary to these study results, the estimates found by both authors declined over the intervals. Imboonta et al (2007) have reported greater heritability estimates than in the present study, using multitrait analysis. Its values were 0.16, 0.16 and 0.18 for the first, second and third WEI, respectively.…”
Section: Resultscontrasting
confidence: 75%
“…Higher heritabilities were, however, reported ranging from 0.11 to 0.44 (Ten Napel et al, 1995;Adamec and Johnson, 1997;Hanenberg et al, 2001;Imboonta et al, 2007;Cavalcante-Neto et al, 2008b).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Compared with 12,599 Thai Landrace sows recorded between's 1993-2005, TNB and SB was 10.03+2.64 and 0.21+0.59 (Imboonta et al, 2007). While, Moeller et al, (2004) stated between's 1997-1999 that TNB was 11.05+1.49, with range 1-25 pigs, and NBA was 9.96+1.38, with range 0-21 pigs.…”
Section: Discussionmentioning
confidence: 83%
“…The piglet number and its related traits were decline on subsequent parity (Imboonta et al, 2007). Here, TCTC haplotype was significantly focused on SB that were due to effects of uterine environment in late gestation, length of the farrowing period, and management at parturition, that may result in SB pigs (Moeller et al, 2004).…”
Section: Fth Polymorphisms Discovery and Associationmentioning
confidence: 99%